Joan of Arc in the English imagination, 1429-1829 - Orgelfinger, Gail Margaret, 1951- (The Pennsylvania State University Press, 2019)
"Explores representations of Joan of Arc in English culture from 1429 until the early nineteenth century, examining the factors that shaped retellings of her military successes and execution"--Provided by publisher